Children’s life in superdiversity contexts: impacts on the construction of a children’s citizenship – the Portuguese case - Ferreira, J. M. L. (Current Sociology, 2022)
This article develops a reflexive and interpretive analysis of the life of children in superdiversity contexts, systematizing some of its impacts on the construction of a children’s citizenship, with particular reference to the Portuguese case. The article promotes the conceptual construction of the child in the 21st century through the correlation of qualitative analysis variables based on a multidisciplinary and/or interdisciplinary theoretical framework. The article introduces the child protection system in Portugal within a framework of European and international influences. It identifies the indicators present in public policies and in the social welfare system that affect child protection in a cross-analysis with the professional practices that intervene with children and families. The author addresses the questions of the ecosocial dimension in the territorialized intervention of family policies in contemporary and multiple approaches to superdiversity. For policy-makers and practitioners in local government, NGOs and social services, appreciating the dimensions and dynamics of superdiversity has profound implications for how they might understand and deal with modes of difference and their interactions within the population. The article concludes with a systematization on the current problems regarding the child as a citizen in contemporary society.